Therapeutic efficacy and mechanisms of gentiopicroside in various diseases - Kui, Ling; Wang, Guoyun; Huang, Jinqun; Yang, Xiaonan; Yu, Jinshi; Li, Xi; Peng, Huaming; Leng, Bingfeng; Jiao, Yinming; Zhang, Zhanjiang (Frontiers in Pharmacology, 2025)
Gentiopicroside (GPS), a secoiridoid glycoside found in traditional medicinal plants such as Gentiana scabra Bunge, exhibits diverse pharmacological properties, including anti-inflammatory, antioxidant, neuroprotective, hepatoprotective, antidiabetic, antitumor, and skin disease-modulating effects. This review consolidates current research on GPS, highlighting its mechanisms of action across various diseases. GPS modulates key signaling pathways, such as NF-κB and MAPK, to suppress pro-inflammatory cytokines and oxidative stress. It activates the Keap1-Nrf2 pathway to enhance cellular antioxidant defenses and exhibits direct free radical scavenging capabilities. In neurodegenerative diseases like Alzheimer’s and Parkinson’s, GPS reduces amyloid-β accumulation and dopaminergic neuron loss, respectively. Its hepatoprotective effects include mitigating chemical- and alcohol-induced liver damage by regulating lipid metabolism and reducing fibrosis. GPS also improves insulin sensitivity in diabetes and inhibits tumor cell proliferation and migration. Additionally, GPS shows promise in treating skin conditions like psoriasis and enhancing wound healing. Despite its therapeutic potential, current evidence is limited by methodological gaps, preclinical inconsistencies and weak clinical evidence (no large-scale randomized controlled trials [RCTs]). Challenges such as low bioavailability and the need for further clinical validation remain. Future research should focus on optimizing GPS formulations and conducting rigorous RCTs, standardizing botanical drug characterization, translating preclinical findings into effective therapies.